Dynamic Learning Rate Schedules and Stability in Adversarial Code Generation - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: What is the correlation between dynamic learning rate schedules and the stability of code generation models when evaluated on adversarial examples from LiveCodeBench. 4 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.0/10. This report is a machine-generated literature
Machine-generated literature synthesis.